Malaria: change in a variety of clinical manifestations in Eastern India (Bangladesh Journal of Medical Science, 2014)
Objective: We had undertaken this study to find out the change in variety of clinical presentations in which a patient suffering from malaria could present. Materials and methods: In a retrospective, cross-sectional and observational study first 100 admitted malaria patients were taken in a tertiary hospital cum medical college at Kolkata, India from August 2009 to July 2011. Their clinical profile were noted and analysed. Results: A variety of clinical pattern was noted in various combinations, starting from fever, chill, and rigor to even hematemesis and rash. Change was noted in pattern of fever and other manifestations. Conclusion: Each patient suffering from malaria could present with a variety of clinical features with some specific patterns in specific cases as discussed. Treatment of malaria in Eastern India was efficacious but costly. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18298 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.150-154